Force distribution of a cylindrical grip differs between dominant and nondominant hand in healthy subjects - Pingel, Isabel; Lorz, Daniel; Beier, Justus; Horch, Raymund E.; Arkudas, Andreas; Cai, Aijia (Archives of Orthopaedic and Trauma Surgery, 2018)
INTRODUCTION: Grip strength and load distribution of the hand are important parameters for evaluating hand function. The purpose of this study was to analyze and compare grip force and load distribution of dominant and nondominant hands in right-handed healthy subjects. METHODS: Gripping measurements were performed on 40 healthy right-handed subjects using a cylindrical gripping device. Two different cylinders with circumferences of 150 mm (small cylinder) and 200 mm (large cylinder), respectively, were used for the measurements. Subjects were assigned to either the small or the large cylinder with respect to their hand size. Maximum and mean force applied during three intervals of gripping as well as the percent contribution of each digit, thenar, and hypothenar in relation to the total load applied were acquired. Values of dominant and nondominant hands were compared. RESULTS: Percent contribution of mean grip strength differed for the thumb (p = 0.007), ring finger (p < 0.001), little finger (p = 0.047), and palm (p < 0.001). Comparing the dominant and nondominant side, the dominant hand showed a lower contribution of the thumb, ring finger, and little finger, but a higher contribution of the palm. When analyzing maximum grip, percent contribution of the small fingers was equal between dominant and nondominant side (p = 0.1). Differences between dominant and nondominant thumb, ring finger, and palm persisted (p = 0.007, p = 0.001, p = 0.005, respectively). No differences could be shown for the index finger, middle finger, thenar, and hypothenar when analyzing both mean and maximum force. DISCUSSION AND CONCLUSION: Percent contribution of the thumb and the fingers to total grip strength differed between dominant and nondominant hands with a change in distribution when assessing maximum grip force. In right-handed subjects, thumb and ring finger have important roles during gripping.
EVALuna2:211471